Controlling swelling/deswelling of stimuli-responsive hydrogel nanofilms in electric fields. Issue 40 (19th September 2016) - Longo, Gabriel S.; Olvera de la Cruz, Monica; Szleifer, Igal
Abstract : Under an applied electric field, pH-responsive hydrogel nanofilms display swelling–deswelling transitions as pH increases. Abstract : The swelling/deswelling transition of pH-sensitive, electrode-grafted, hydrogel nanofilms when exposed to electric fields is studied by theoretical analysis. In acidic conditions, the response of these films to changes in pH is dominated by network–surface interactions, while intra-network electrostatic repulsions, which are highly modulated by the adsorption of salt ions, determine material response at a higher pH. Film thickness is a non-monotonic function of solution pH and displays a local maximum, a local minimum or both, depending on the salt concentration and the applied voltage. We suggest the use of these materials in the development of biosensors and control of enzyme activity.